2021
DOI: 10.1002/jms.4698
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of a compound despite the presence of an isobaric interference by using in‐source Collision Induced Dissociation and tandem mass spectrometry

Abstract: The presence of an isobaric contaminant can drastically affect MS and MS/MS patterns leading to erroneous structural and quantitative analysis, which is a real challenge in mass spectrometry. Herein, we demonstrate that MS and MS/MS structural analysis of a compound can be successfully performed despite the presence of an isobaric interference with as low as few millidaltons mass difference by using pseudo‐MS3. To this end, in‐source collisional excitation (in‐source CID) and the Survival Yield (SY) technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Nevertheless, in the last two decades, many MS/MS strategies have been developed to solve this problem by allowing the characterization and quantification of isomers and/or isobars in mixtures via a standardized approach, applicable to different compounds [ 11 ]. Among these strategies, the most promising and interesting for a widespread application in the recognition of isomers are based on (1) energy-resolved tandem mass experiments [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] and (2) kinetics of the ion-molecule interaction [ 20 , 21 , 22 ], even if the latter are limited to the use of the ion trap. Summarizing the reported results, the discrimination between isomers was achieved by optimizing the selection of precursor ion, its fragmentation through collision induced dissociation (CID) mechanism and the analysis of fragmented ions produced.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in the last two decades, many MS/MS strategies have been developed to solve this problem by allowing the characterization and quantification of isomers and/or isobars in mixtures via a standardized approach, applicable to different compounds [ 11 ]. Among these strategies, the most promising and interesting for a widespread application in the recognition of isomers are based on (1) energy-resolved tandem mass experiments [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] and (2) kinetics of the ion-molecule interaction [ 20 , 21 , 22 ], even if the latter are limited to the use of the ion trap. Summarizing the reported results, the discrimination between isomers was achieved by optimizing the selection of precursor ion, its fragmentation through collision induced dissociation (CID) mechanism and the analysis of fragmented ions produced.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it might be that a fragment is consistent with two isobars simultaneously from a pure mass loss perspective, e.g., the benzyl fragment C 6 H 5 + could arise from either one (or both) of two co-fragmented aromatic precursors. Only a few studies have explicitly addressed the problem for DI-MS, e.g., it is reported that ion mobility 31 or "collisional purification" 32,33 on MS 3 -or pseudo-MS 3capable instruments can resolve chimeras.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, ISF provides an additional collision stage prior to the mass analyzer’s work, which enables acquisition of abundant mass spectral information even from the soft electrospray ionization (ESI) source. , Since fragmentation of analytes in ISF is similar to that in CID of tandem mass spectrometry (MS/MS), ,, ISF has been employed as an inexpensive collision-induced fragmentation generator to obtain MS/MS spectra of compounds in a mass spectrometer with only a single-stage mass analyzer. , Therefore, ISF has been used for the characterization of organic compounds and biomacromolecules, such as 1,4-dihydropyridine calcium antagonists and glycopeptides . In recent years, ISF has also been coupled with high resolution mass spectrometry (ISF-HRMS) to screen the compounds that can generate characteristic neutral loss (NL) or fragment ion (FI) in ion source from biological samples. , For instance, since some modified metabolites including acetylated, glucosidated, glucuronidated, sulfated, and ribose conjugated can produce specific NL fragments in ion source, an ISF-HRMS method has been developed for profiling metabolites with specific groups in human urine samples .…”
mentioning
confidence: 99%
“…12,15 Therefore, ISF has been used for the characterization of organic compounds and biomacromolecules, such as 1,4-dihydropyridine calcium antagonists 18 and glycopeptides. 19 In recent years, ISF has also been coupled with high resolution mass spectrometry (ISF-HRMS) to screen the compounds that can generate characteristic neutral loss (NL) or fragment ion (FI) in ion source from biological samples. 7,20−23 For instance, since some modified metabolites including acetylated, glucosidated, glucuronidated, sulfated, and ribose conjugated can produce specific NL fragments in ion source, an ISF-HRMS method has been developed for profiling metabolites with specific groups in human urine samples.…”
mentioning
confidence: 99%